Predicting graduate employment: the relationship among social skills, performance and motivation in cosmetology education graduates - Megasari, Dindy Sinta; Puspitorini, Arita; Lutfiati, Dewi (Jurnal Pendidikan Teknologi Kejuruan, 2023)
There have been many studies focusing on graduate tracing. However, they were still determining how likely the graduates will work following their interests and the fields of knowledge they have studied. This study aimed at gaining improved awareness of cosmetology education graduates' employment readiness concerning social skills, performance, and work motivation. This explanatory research used the entire research population of the last two years, as many as 70 graduates. Data collection was carried out using a questionnaire on each variable studied. While the analysis method used a structural equation model (Warp-PLS) to confirm the model's accuracy while testing the influence of variables on other variables and verifying that the instruments utilized were valid and dependable. The results proved that social skills, performance and work motivation directly and significantly affect graduate job readiness. Graduates' social skills and performance also affected job readiness in the field. The social skills of graduates were higher in influence than the performance and motivation of graduates in work readiness, with a difference of 0.391. These results implied a need to improve soft communication skills and spiritual provision in addition to the competencies that graduates already have.